PERAN LEMBAGA ISLAM DALAM MENGENTASKAN KEMISKNAN (Studi Kasus Pada Baitul Maal Hidayatullah Cabang Malang) - Afifah, Fajri Mas; Hoetoro, Arif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Poverty is a condition in which an individual can’t fill their basic needs. Islam considers that poverty is a problem that must be resolved quickly. Islam has solutions to reduce poverty by working or an individual obligation for themselves and Zakah, Infaq, Sedekah, and Waqf (ZISWAF) or an individual obligation foranother person. ZISWAF is an Islamic income redistribution. Islam has an institution that collecting, utilizing, and distributing ZISWAF namely Baitul Maal. Baitul Maal Hidayatullah choose to distribute their funds through four main programs, they are: religious proselytizing, education, economic, and social humanity. BMH also has a different distribution system, they distribute their fund through the third party namely da’i or coordinator, aplicating this system expected that the given fund can be allocated as a given function. Keyword: Poverty, ZISWAF, Baitul Maal